Psychological hardness and its role in facing stressful life events among students of the Faculty of Education at the University of Idlib - Shaheen, Ahmad Abdl AL Majid (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the level of psychological toughness among a sample of students of the classroom teacher and psychological counselling departments in the College of Education at the University of Idlib, and to reveal the correlation between stressful life events and psychological toughness among a sample of students of the classroom teacher and psychological counselling departments in the College of Education, University of Idlib. A random sample was drawn from the classroom teacher and psychological counselling departments (first year and third year), where the total number of the sample amounted to (166) male and female students. To achieve the objectives of the study, a measure of psychological hardness and a measure of stressful life events were applied, and the study reached several results: - Level of hardness Psychology among the study sample is high - there are no statistically significant differences in the level of psychological hardness among the study sample according to the variable of gender and academic level - the level of stressful life events in the study sample came to a medium degree, and there are statistically significant differences in the level of stressful life events for the benefit of females, In favour of first year students, there is no correlation between the psychological hardness variables and stressful life events.
Keywords: psychological toughness; stressful life events; students of the College of Education